Effect of Dilution Ratio on Wear Resistance in Multi-Layer Hard-Facing Weldments - Chanchana, Atthakorn; Srisawat, Manus; Sangkatip, Rittichai; Kaewwichit, Jesada (Journal of Advanced Development in Engineering and Science, 2023)
This research aimed to investigate the effects of the dilution ratio on wear resistance in multi-layer, hard-facing weldments made of carbon steel grade AISI 1045. The specimen was welded using the gas metal arc welding process (GMAW). This analysis was divided into two parts. The first part analyzed the hard-facing sound weld, dilution ratios, and chemical composition of each layer of hard facing, while the second part involved testing the mechanical properties, including hardness and resistance to wear. The test results can be summarized as follows: Welding repairs should only be welded in one layer to provide a low dilution ratio when hard surface deposits are made with the metal arc. Additionally, it was discovered that multilayer welding tends to decrease the amount of silicon and chromium elements, thereby reducing wear resistance.